FACTORS INFLUENCING ENDORPHIN MASSAGE ON BREAST MILK PRODUCTION AMONG BREASTFEEDING MOTHERS WITH INFANTS AGED 0–6 MONTHS - nuripa kasani; Sellia Juwita; Nurmaliza (LPPM Universitas Abdurrab, 2025)
ackground: Breast milk (ASI) is a natural source of nutrition that contains essential nutrients for infant growth and development, including intelligence. One method to enhance breast milk production is endorphin massage. Endorphin massage is a gentle massage applied around the neck, back, and arms to provide comfort and relaxation. Objective: This study aimed to analyze the factors influencing the effectiveness of endorphin massage on breast milk production among breastfeeding mothers with infants aged 0–6 months. Methods: This research employed an analytical quantitative method with a cross-sectional approach. The study was conducted in the working area of Payung Sekaki Public Health Center, Pekanbaru City, from July 30 to June 15, 2025. A total of 87 breastfeeding mothers were selected using purposive sampling. Data were collected using questionnaires and analyzed with the Chi-Square test. The variables studied included maternal knowledge, maternal attitude, and husband’s support. Results: The findings showed that the majority of respondents had good knowledge (69.0%), positive attitudes (89.7%), received husband’s support (92.0%), and experienced smooth breast milk production (93.1%). Statistical tests indicated a significant relationship between all three variables and breast milk production (p-value < 0.05). Conclusion: Maternal knowledge, maternal attitude, and husband’s support play an important role in the success of endorphin massage in increasing breast milk production. It is recommended that health workers provide more education to mothers and husban